2019
DOI: 10.1111/1750-3841.14975
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the peptides with calcium‐binding capacity from tilapia (Oreochromis niloticus) skin gelatin enzymatic hydrolysates

Abstract: The aim of this study was to isolate and identify the peptides with calcium‐binding capacity from the different tilapia skin gelatin enzymatic hydrolysates. The complex protease was selected and its hydrolysates were further separated using gel filtration chromatography (Sephadex G‐25) and reverse phase high‐performance liquid chromatography. Two purified peptides with strong calcium‐binding capacity were identified as Tyr‐Gly‐Thr‐Gly‐Leu (YGTGL, 509.25 Da) and Leu‐Val‐Phe‐Leu (LVFL, 490.32 Da). The calcium‐bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…After introducing calcium ions, FA6-calcium chelate exhibited regularly ordered and tightly aggregated sheets or block structures. This conclusion is similar to the work of Liu et al, who showed that the peptides YGTGL and LVFL interacted with calcium ions to generate novel molecules in flake or block structures . It is possible that this came about as a result of the interaction between calcium ions and carboxyl groups, which attracted FA6 and created an aggregate connected by a hydrogen bond.…”
Section: Resultssupporting
confidence: 89%
“…After introducing calcium ions, FA6-calcium chelate exhibited regularly ordered and tightly aggregated sheets or block structures. This conclusion is similar to the work of Liu et al, who showed that the peptides YGTGL and LVFL interacted with calcium ions to generate novel molecules in flake or block structures . It is possible that this came about as a result of the interaction between calcium ions and carboxyl groups, which attracted FA6 and created an aggregate connected by a hydrogen bond.…”
Section: Resultssupporting
confidence: 89%
“…These peptides include GY (17.94 µg μmole −1 ) and EG (13.84 µg μmole −1 ), which were isolated from whey protein hydrolysate [ 6,7 ] ; FY (42.28 µg μmole −1 ), which was isolated from unicellular algae ( Schizochytrium sp .) protein hydrolysate [ 29 ] ; and YGTGL (38.72 µg μmole −1 ) and LVFL (38.99 µg μmole −1 ), which were isolated from tilapia skin gelatin hydrolysate [ 8 ] (Table 1). Based on the binding capacity, the calcium‐binding efficiency was calculated as one mole of KFP‐1 binding 0.73 moles of calcium.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Food protein derived peptides released by enzymatic hydrolysis or by fermentation processes can form peptide‐calcium complexes to enhance the bioavailability and absorption of calcium. Known food sources of these peptides include milk, [ 6,7 ] fish byproducts, [ 8,9 ] wheat germ, [ 10 ] and algae. [ 11 ] For example, caseinophosphopeptides (CPPs) were the first and the most extensively studied calcium‐binding peptides from the casein protein from milk.…”
Section: Introductionmentioning
confidence: 99%
“…Following complexation, the extent of peptide chelation of calcium ions is elucidated by quantification of Ca 2+ in the supernatant using AAS [ 38 ]. This method has since been modified to incorporate the binding activity of several calcium-chelating peptides, such as those derived from Antarctic krill and tilapia skin gelatin enzymatic hydrolysates, including the use of flame AAS instead [ 39 , 40 ].…”
Section: Methods For the Determination Of The Mineral-chelating Acmentioning
confidence: 99%